The Role of School Environment on the Sustainable Development of Pre-Schoolers’ Motor Creativity - Despoina Ourda; Anna Kavoukoglou; Athanasios Gregoriadis; Vassilis Barkoukis (Sports, 2025)
This study examined the influence of student–teacher relationships and school infrastructure on preschool children’s motor creativity, encompassing fluency, originality, and imagination. Twenty teachers completed the Student–Teacher Relationship Scale for 200 children (10 children per teacher). The research team recorded aspects of the school’s physical environment through Movement Play Scale and assessed children’s motor creativity via the Thinking Creatively in Action and Movement test. The results revealed that dimensions of the student–teacher relationship, such as conflict and dependency, negatively impacted fluency, and originality components of motor creativity. Contrary to expectations, teacher participation in movement activities did not significantly contribute to motor creativity, potentially due to over-direction limiting children’s autonomy. Similarly, the school’s infrastructures were negatively linked to fluency and originality. The findings underscore the importance of nurturing autonomy-supportive environments and balancing guidance with opportunities for independent exploration. Teachers should also invest in adaptable educational spaces to foster creativity without encouraging dependency. This study emphasizes the critical role of supportive relational and environmental factors in shaping preschool children’s creative movement abilities.